2019
DOI: 10.1016/j.tcs.2019.07.014
|View full text |Cite|
|
Sign up to set email alerts
|

The orthogonal colouring game

Abstract: We introduce the Orthogonal Colouring Game, in which two players alternately colour vertices (from a choice of m ∈ N colours) of a pair of isomorphic graphs while respecting the properness and the orthogonality of the colouring. Each player aims to maximise her score, which is the number of coloured vertices in the copy of the graph she owns. The main result of this paper is that the second player has a strategy to force a draw in this game for any m ∈ N for graphs that admit a strictly matched involution. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…of vertices in 2-orbits of V under the action of σ. Andres et al [2] defined an involution σ of G to be strictly matched if (SI 1) the set F 1 (G) induces a (possibly empty) complete graph and, (SI 2) for every v ∈ F 2 (G), we have the (matching) edge vσ(v) ∈ E.…”
Section: Notation and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…of vertices in 2-orbits of V under the action of σ. Andres et al [2] defined an involution σ of G to be strictly matched if (SI 1) the set F 1 (G) induces a (possibly empty) complete graph and, (SI 2) for every v ∈ F 2 (G), we have the (matching) edge vσ(v) ∈ E.…”
Section: Notation and Definitionsmentioning
confidence: 99%
“…Andres et al [2] proved that a graph G admits a strictly matched involution if and only if its vertex set V (G) can be partitioned into a clique C and a set inducing a graph that has a perfect matching M such that:…”
Section: Recognising Graphs Admitting a Strictly Matched Involutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Players may gain points in a myriad of ways, all depending on the rules of the game. For example, in the orthogonal colouring game on graphs [1], a player's score is equal to the number of coloured vertices in their copy of the graph at the end of the game, i.e., each player gets one point for each coloured vertex in their copy of the graph. Recently, the papers [12,13,14] have started to build a general theory around scoring games.…”
Section: Introductionmentioning
confidence: 99%
“…A perfect 2-orthogonal colouring is simply called a perfect orthogonal colouring. Perfect orthogonal colourings are of particular importance because they have applications to independent coverings [7] and scoring games [1]. It is now shown that perfect k-orthogonal colourings can build on the applications of (n, k, 1)-transversal designs.…”
Section: Introductionmentioning
confidence: 99%